Describe and Draw Game Towards Students’ Speaking Competence - I Made Permadi Utama (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2019)
The aim of this study is to find the effect of Describe and Draw game towards students’ speaking competence at SMAN 2 Gerung. This study used a quasi-experimental with post-test only non-equivalent control group design. The population of this study was second-grade students of SMAN 2 Gerung. The writer took two classes chosen as experimental group and control group. Experimental group was treated by using Describe and Draw game and control group was treated by using Word Match game. Based on the result of the study, it was found that Describe and Draw Game has a significant effect towards students’ speaking competence at SMAN 2 Gerung.